A modified aerobic composting composite membrane and its preparation method and use method
By stacking modified polyester fiber layers and polydopamine in the membrane, the problem of poor water vapor transmission effect in membrane-covered aerobic compost technology is solved, and higher moisture permeability and stronger nitrogen-retaining and ammonia resistance are achieved, ensuring the quality and environmental protection of the compost products.
Patent Information
- Application Number
- CN202411876256.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing membrane-covered aerobic compost technology has poor water vapor permeability, resulting in the moisture content of the compost product being higher than the standard, affecting the quality of fertilizers, and at the same time increasing the permeability of ammonia and increasing the risk of environmental pollution.
A composite film of a modified polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer is adopted, and polydopamine is wrapped on the surface of the first polyester fiber layer. A stable film structure is formed through self-polymerization of polydopamine, thereby improving the moisture permeability of the film and nitrogen-retaining and ammonia resistance.
The modified film can significantly improve moisture permeability, reduce ammonia permeability, meet the quality standards of fertilizer products, and maintain the waterproof, water splashing and breathability of the original film.
Smart Images

Figure CN119329162B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic solid waste treatment and comprehensive utilization, and specifically relates to a modified aerobic composting composite membrane and a preparation method and a use method thereof. Background Art
[0002] In recent years, an aerobic composting composite membrane suitable for organic solid fermentation has been developed, including a three-layer structure: the inner and outer layers are made of polyester fiber, and the middle layer is made of expanded polytetrafluoroethylene (ePTFE) material. The membrane has good air permeability, moisture permeability and waterproofing functions, and can also reduce the emission of odorous gases during the composting process. After the membrane covers the surface of the compost material, it can protect the compost material from the outside, so that it is not affected by the climate or wet by rain, and a microenvironment is formed inside the membrane that is conducive to microorganisms converting organic matter into high-quality fertilizers. At the same time, air and water vapor can be discharged outside the membrane, while odor, dust, pathogens, etc. are effectively isolated inside the membrane. It is a harmless and low-odor emission technical means.
[0003] However, the current membrane-covered aerobic composting has the problem of poor water vapor permeability. Chen et al. (Waste Management, 2021, 131, 1-9) used membrane-covered aerobic composting technology to treat livestock and poultry manure. After composting, the moisture content of the final product was still as high as 59% or more, which did not meet the compost product quality requirements of the "Technical Specifications for Composting Livestock and Poultry Manure" (NY / T3442-2019) (moisture content ≤ 45%), which will affect the subsequent application as a fertilizer product. Although the moisture permeability of the membrane can be increased by increasing the pore size, this method often leads to a simultaneous increase in the permeability of odors such as ammonia, thereby aggravating the environmental pollution of the livestock and poultry manure treatment process. At the same time, it also causes the loss of nutrients such as nitrogen, which is not conducive to promoting the green and high-quality development of animal husbandry. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a modified aerobic composting composite membrane and a preparation method thereof. The modified aerobic composting composite membrane provided by the present invention can simultaneously improve the membrane's moisture permeability and nitrogen retention and ammonia barrier efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a modified aerobic composting composite membrane, comprising a modified polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence;
[0007] The modified polyester fiber layer comprises a first polyester fiber layer and polydopamine wrapped around each fiber on the surface of the first polyester fiber layer.
[0008] Preferably, the thickness of the first polyester fiber layer is 0.38-0.45 mm; the thickness of the polytetrafluoroethylene layer is 4-30 μm; and the thickness of the second polyester fiber layer is 0.38-0.45 mm.
[0009] The present invention also provides a method for preparing the modified aerobic composting composite membrane described in the above technical solution, comprising the following steps:
[0010] pre-treating the aerobic composting base film to obtain a pre-treated base film;
[0011] The aerobic composting base film comprises a first polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence;
[0012] The pretreated base film is placed in a dopamine hydrochloride solution so that the first polyester fiber layer of the pretreated base film contacts the dopamine hydrochloride solution and the second polyester fiber layer contacts the air, and then the polydopamine surface is self-polymerized to obtain the modified aerobic composting composite film.
[0013] Preferably, the dopamine hydrochloride solution is obtained by mixing a Tris-HCl buffer solution and dopamine hydrochloride.
[0014] Preferably, the concentration of the Tris-HCl buffer solution is 50-100 mmol / L; the pH value of the Tris-HCl buffer solution is 8.2-8.8; and the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 0.1-2 g / L.
[0015] Preferably, the time for the self-polymerization of the polydopamine surface is 1 to 4 h.
[0016] Preferably, the polydopamine surface self-polymerization is carried out under stirring conditions, and the stirring is magnetic stirring; the rotation speed of the magnetic stirring is 200~500 r / min.
[0017] Preferably, after the polydopamine surface is self-polymerized, the method further comprises washing the composite membrane on which the polydopamine is polymerized with water and then drying it.
[0018] Preferably, the drying temperature is 60-80° C., and the drying time is 8-24 h.
[0019] The present invention also provides a method for using the modified aerobic composting composite membrane described in the above technical solution. When the modified aerobic composting composite membrane is used, the modified polyester fiber layer is used as the innermost layer.
[0020] The present invention provides a modified aerobic composting composite membrane, comprising a modified polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence; the modified polyester fiber layer comprises a first polyester fiber layer and polydopamine wrapped around each fiber on the surface of the first polyester fiber layer. During the membrane-covered aerobic composting process, a condensed water layer will be generated on the inner surface of the membrane due to the vapor pressure difference between the inside and outside of the membrane. In the present invention, before modification (i.e., the first polyester fiber layer), the vaporization of the condensed water under the membrane all comes from free water, while after the membrane is modified, most of the water molecules in contact with or around the polydopamine are activated as intermediate water. Since the vaporization enthalpy of intermediate water is much lower than that of free water, the energy required for the vaporization of the condensed water under the membrane will be greatly reduced, thereby increasing the moisture permeability of the membrane. Moreover, since polydopamine contains a large number of hydroxyl groups and amino groups, it can form hydrogen bonds with ammonia, which hinders the diffusion of ammonia in the membrane to the outside, and after the modification with polydopamine, the coverage area of condensed water under the membrane is increased, so that the amount of ammonia directly contacting the inner surface of the membrane and diffusing to the outer surface of the membrane through the pores is reduced, and the amount of ammonia dissolved in the water film is increased, further enhancing the nitrogen retention and ammonia barrier efficiency of the membrane. However, non-polar gases such as nitrogen and oxygen will not interact with the groups in polydopamine, and are not easy or difficult to dissolve in water. Therefore, the permeability of gases such as nitrogen and oxygen only changes slightly due to the influence of the porosity of the membrane, so the modified aerobic composting composite membrane provided by the present invention still has good (air) permeability. In addition, the present invention only modifies the surface of the first polyester fiber layer with polydopamine, and the surface of the second polyester fiber layer (as the outermost layer when used) is still hydrophobic, which can maintain the waterproof and splash-proof properties of the original membrane; after modification, dust, bacteria, pathogens, etc. can still be well isolated in the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The XPS spectra of unmodified aerobic composting composite membrane and modified aerobic composting composite membrane;
[0022] Figure 2 The contact angle diagrams of unmodified aerobic composting composite film and modified aerobic composting composite film;
[0023] Figure 3 The scanning electron micrographs of the unmodified aerobic composting composite membrane and the polydopamine modified membrane at different self-polymerization times are shown in FIG. Figure 3 (a) and (e) are scanning electron microscope images of the unmodified aerobic composting composite membrane. Figure 3 (b) and (f) are scanning electron micrographs of the membrane after 1 h of polydopamine self-polymerization. Figure 3 (c) and (g) are scanning electron microscopy images of the membrane after 2 h of polydopamine self-polymerization. Figure 3 (d) and (h) are scanning electron microscopy images of the membrane after 4 h of polydopamine self-polymerization;
[0024] Figure 4The porosity diagrams of unmodified aerobic composting composite membrane and modified aerobic composting composite membrane at different self-polymerization times;
[0025] Figure 5 The water vapor permeability change diagram of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane with different self-polymerization time under the simulated composting condition;
[0026] Figure 6 The graphs are the changes in ammonia outlet concentration and the changes in ammonia retention rate of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times in the ammonia barrier experiment;
[0027] Figure 7 This is a graph showing the changes in nitrogen and oxygen gas permeability of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times. DETAILED DESCRIPTION
[0028] The present invention provides a modified aerobic composting composite membrane, comprising a modified polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence;
[0029] The modified polyester fiber layer comprises a first polyester fiber layer and polydopamine wrapped around each fiber on the surface of the first polyester fiber layer.
[0030] As an embodiment, the thickness of the first polyester fiber layer is 0.38-0.45 mm, and in a specific embodiment, the thickness of the first polyester fiber layer may be 0.39 mm. As an embodiment, the thickness of the polytetrafluoroethylene layer is 4-30 μm, and in a specific embodiment, the thickness of the polytetrafluoroethylene may be 6 μm. As an embodiment, the thickness of the second polyester fiber layer is 0.38-0.45 mm, and in a specific embodiment, the thickness of the second polyester fiber layer may be 0.39 mm.
[0031] As an embodiment, the porosity of the modified aerobic composting composite membrane is 57-63%.
[0032] The polydopamine in the present invention has a strong bonding effect with the membrane matrix, can form a firm bond, is not easy to fall off, and can make the modified aerobic composting composite membrane have a better moisture permeability effect and nitrogen retention and ammonia barrier efficiency for a long time.
[0033] The present invention also provides a method for preparing the modified aerobic composting composite membrane described in the above technical solution, comprising the following steps:
[0034] pre-treating the aerobic composting base film to obtain a pre-treated base film;
[0035] The aerobic composting base film comprises a first polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence;
[0036] The pretreated base film is placed in a dopamine hydrochloride solution so that the first polyester fiber layer of the pretreated base film contacts the dopamine hydrochloride solution and the second polyester fiber layer contacts the air, and then the polydopamine surface is self-polymerized to obtain the modified aerobic composting composite film.
[0037] The invention pretreats the aerobic composting base film to obtain the pretreated base film.
[0038] As an embodiment, the pretreatment includes alcohol washing, water washing and drying in sequence. Specifically, the pretreatment is: immersing the aerobic compost base film in ethanol for 1 to 4 hours, taking it out and rinsing it with deionized water for multiple times, then immersing it in deionized water for ultrasonic treatment for 5 to 20 minutes, and finally drying it. As an embodiment, the frequency of the ultrasonic treatment is 424 Hz. As an embodiment, the drying temperature is 60 to 80°C and the time is 8 to 24 hours.
[0039] After obtaining the pretreated base film, the present invention places the pretreated base film in a dopamine hydrochloride solution, so that the first polyester fiber layer of the pretreated base film contacts the dopamine hydrochloride solution, and the second polyester fiber layer contacts the air, and then the polydopamine surface is self-polymerized to obtain the modified aerobic composting composite film.
[0040] As an embodiment, the dopamine hydrochloride solution is obtained by mixing a Tris-HCl buffer solution and dopamine hydrochloride.
[0041] As an embodiment, the preparation of the Tris-HCl buffer solution comprises the following steps:
[0042] After dissolving tris(hydroxymethyl)aminomethane (Tris) in deionized water, the pH value was adjusted to 8.2-8.8 with hydrochloric acid, and the volume was fixed to obtain a Tris-HCl buffer solution.
[0043] In a specific embodiment, tris (hydroxymethyl)aminomethane (Tris) is dissolved in deionized water, the pH value is adjusted to 8.5 with hydrochloric acid, and the volume is fixed to obtain a Tris-HCl buffer solution.
[0044] As an embodiment, the concentration of the Tris-HCl buffer solution is 50-100 mmol / L. In a specific embodiment, the concentration of the Tris-HCl buffer solution can be 50 mmol / L, 60 mmol / L, 70 mmol / L, 80 mmol / L or 90 mmol / L.
[0045] As an embodiment, the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 0.1-2 g / L. In a specific embodiment, the concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 0.5 g / L, 1.0 g / L, 1.5 g / L or 2.0 g / L.
[0046] As an embodiment, the polydopamine surface self-polymerization is carried out under stirring conditions; the stirring is magnetic stirring; the rotation speed of the magnetic stirring is 200~500 r / min. In a specific embodiment, the rotation speed of the magnetic stirring can be 300 r / min.
[0047] As an embodiment, the time for the self-polymerization of the polydopamine surface is 1 to 4 hours. In a specific embodiment, the time for the self-polymerization of the polydopamine surface can be 1 hour, 2 hours, 3 hours or 4 hours.
[0048] As an embodiment, after the polydopamine surface is self-polymerized, the composite membrane with the polydopamine polymerized on the surface is washed with water and then dried.
[0049] As an embodiment, the water washing is performed until no excess dopamine hydrochloride solution remains on the surface.
[0050] As an implementation mode, the drying temperature is 60-80° C., and the drying time is 8-24 h.
[0051] The present invention utilizes dopamine to achieve self-polymerization and deposition under weak alkaline conditions (pH value 8.2-8.8) to form polydopamine, and the fibers on the surface of the first polyester fiber layer of the unmodified aerobic composting base film wrap the polydopamine. In this process, the film substrate is not damaged, and the outer layer of the film is still a hydrophobic surface, so the original good waterproof, splash-proof, tensile and heat-insulating properties can be maintained. In addition, the film preparation method of the present invention is simple, and the deposition of dopamine can be achieved through a very simple surface deposition method, without the need for other special equipment, easy to operate and control, short reaction process, the deposition solution can be reused many times, low cost, easy to mass produce and industrialize.
[0052] The present invention also provides a method for using the modified aerobic composting composite membrane described in the above scheme. When the modified aerobic composting composite membrane is used, the modified polyester fiber layer is used as the innermost layer.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] S1. Immerse the aerobic composting base membrane (i.e., unmodified aerobic composting composite membrane) with polyester fiber inner and outer layers (the thickness of the inner layer-the first polyester fiber layer is 0.39 mm, and the thickness of the outer layer-the second polyester fiber layer is 0.39 mm) and the middle layer is a polytetrafluoroethylene layer (the thickness of the polytetrafluoroethylene layer is 6 μm) in ethanol for 2 h, take it out and rinse it with deionized water for 5 times, then immerse it in deionized water for ultrasonic treatment (ultrasonic frequency is 424 Hz) for 10 min, and finally place it in a constant temperature drying oven at 60°C to dry for 24 h.
[0056] S2. Preparation of Tris-HCl buffer solution: Dissolve Tris in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH value of the solution to 8.5, and then add a small amount of water to make up the volume to obtain a Tris-HCl buffer solution with a concentration of 50 mmol / L.
[0057] S3. Preparation of dopamine hydrochloride solution: Add dopamine hydrochloride at a concentration of 2 g / L into a Tris-HCl buffer solution and mix thoroughly to obtain a dopamine hydrochloride solution.
[0058] S4. Immerse the inner side of the pretreated membrane (the first polyester fiber layer) downward into the dopamine hydrochloride solution so that it floats on the solution, the inner surface of the membrane is in contact with the solution, and the outer surface of the membrane (the second polyester fiber layer) is in contact with the air. Then stir at a constant temperature of 25°C, the magnetic stirring speed is 300 r / min, and the self-polymerization time of dopamine on the inner surface of the membrane is 1 h. Then take the membrane out of the solution, rinse it thoroughly with deionized water for 5 times, and place it in a vacuum drying oven at 60°C to dry.
[0059] Example 2
[0060] The only difference from Example 1 is that the self-polymerization time of dopamine on the inner surface of the membrane is 2 h.
[0061] Example 3
[0062] The only difference from Example 1 is that the self-polymerization time of dopamine on the inner surface of the membrane is 4 h.
[0063] The modified aerobic composting composite membrane prepared in the present invention is characterized and tested for performance, as follows:
[0064] (1) X-ray photoelectron spectroscopy
[0065] X-ray photoelectron spectroscopy (XPS) was used to test the surface elements of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane. The results are shown in Figure 1 ,from Figure 1It can be seen that a N peak appeared on the inner surface of the membrane, while there was no N element in the unmodified aerobic composting composite membrane, indicating that polydopamine was successfully grafted onto the inner surface of the composite membrane.
[0066] (2) Static contact angle measurement
[0067] The static contact angle test was performed on the inner and outer surfaces of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane (the modified polyester fiber layer is the inner layer) using a contact angle meter. The results are shown in Figure 2 It can be seen that the inner surface of the modified aerobic composting composite membrane changed from hydrophobic to hydrophilic, which also verified that polydopamine was successfully grafted to the inner surface of the composite membrane; and this modification method only modified the inner surface of the membrane without damaging the membrane substrate, and the outer layer of the membrane was still a hydrophobic surface, so it can maintain the original good waterproof, water-repellent, tensile and heat-insulating properties.
[0068] (3) Scanning electron microscopy and porosity testing
[0069] The unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times were tested by scanning electron microscope using a contact angle meter. The results are shown in Figure 3 , Figure 3 (a) and (e) are scanning electron microscope images of the unmodified aerobic composting composite membrane. Figure 3 (b) and (f) are scanning electron micrographs of the membrane after 1 h of polydopamine self-polymerization. Figure 3 (c) and (g) are scanning electron microscopy images of the membrane after 2 h of polydopamine self-polymerization. Figure 3 (d) and (h) are the SEM images of the membrane after 4 h of self-polymerization of polydopamine. Figure 3 b and f), the deposition of polydopamine on the inner surface of the membrane is not obvious; when the self-polymerization time is 2 h ( Figure 3 In the figure (c and g), a layer of colloidal sediment appeared on the surface of each polyester fiber on the inner side of the membrane, and a large number of polydopamine granular particles were observed; when the self-polymerization time was 4 h ( Figure 3 In the images d and h, each polyester fiber on the inner side of the membrane is covered with a relatively thick layer of colloidal deposits, and polydopamine colloidal deposits also appear between some fiber pores. In addition, many larger polydopamine aggregates are observed. This is because the polydopamine particles are prone to agglomeration through non-covalent bonds due to long deposition time. Therefore, the aggregation of polydopamine may also appear between the pores and cause certain effects.
[0070] The porosity of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times were tested by mercury intrusion porosimeter. The results are shown in Figure 4It can be seen that the porosity of the modified membrane gradually decreases with the increase of the self-polymerization time of polydopamine (the porosity of the unmodified aerobic composting composite membrane and the modified membrane with the self-polymerization time of polydopamine of 1, 2, and 4 h are 62.34%, 61.75%, 60.61%, and 57.02%, respectively).
[0071] (4) Moisture permeability test.
[0072] The moisture permeability test of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane with different self-polymerization times under simulated composting conditions is carried out as follows:
[0073] First, weigh about 45 g of 60℃ distilled water into a 50 mL blue-capped bottle, and place the prepared membrane material with the inner layer facing down at the mouth of the blue-capped bottle, so that the water sample is 1 cm away from the inner surface of the membrane, cover it with the headspace cap and tighten it. In order to simulate the water vapor permeation rate under composting conditions, that is, when there is a temperature gradient, place the blue-capped bottle in a water bath and set the water bath temperature to 60℃. After 1 hour of equilibrium, weigh them one by one in a certain order, and then weigh them again in the same order after 24 hours. The water vapor permeability calculation is shown in formula (1):
[0074] (1)
[0075] Where: WVT —Moisture permeability, g / (m 2 24h);
[0076] m 0 —initial mass after 1 h of equilibrium, g;
[0077] m —Final mass after 24 h, g;
[0078] A —Effective test area, m 2 ;
[0079] t —Test time, h.
[0080] Figure 5 The moisture permeability changes of unmodified aerobic composting composite membrane and modified aerobic composting composite membrane with different self-polymerization time under simulated composting conditions. It can be seen that with the increase of polydopamine self-polymerization (polymerization) time, the membrane moisture permeability first increases and then decreases. When the polydopamine self-polymerization time is 2 h, the membrane moisture permeability is the highest, which is 3937.86g / (m 2 ·24 h), the moisture permeability of the composite membrane for aerobic composting was increased by about 10.27% compared with that of the unmodified composite membrane.
[0081] It can be seen from the modified aerobic composting composite membrane synthesized in combination with the three embodiments that there are at least two opposite effects in the self-polymerization modified membrane: ① The steam flux is increased because polydopamine reduces the energy required for the vaporization of condensed water under the membrane. Before modification, the vaporization of condensed water under the membrane all comes from free water, and after the membrane is modified, most of the water molecules in contact with or around polydopamine are activated as intermediate water. Since the vaporization enthalpy of intermediate water is much lower than that of free water, the energy required for the vaporization of condensed water under the membrane will be greatly reduced, so the moisture permeability of the membrane can be increased; ② The moisture permeability is reduced due to the additional resistance to mass transfer. After polydopamine modification, the inner surface of the membrane changes from hydrophobic to hydrophilic, which will cause the condensed water coverage area under the membrane to increase and the open pores that water vapor can directly pass through the membrane surface to decrease. However, this change and the reduction in the porosity of the modified membrane will increase the mass transfer resistance of water vapor, resulting in a decrease in the moisture permeability of the membrane. And when this negative effect exceeds the benefit of providing intermediate water, it will offset each other. Therefore, it is necessary to optimize the self-polymerization time of polydopamine. The research results show that when the self-polymerization time of polydopamine is 2 h, it is most suitable. When the self-polymerization time increases to 4 h, the moisture permeability of the membrane is only increased by 3.86% compared with the unmodified aerobic composting composite membrane.
[0082] (5) Ammonia gas barrier test
[0083] The ammonia gas barrier performance of the unmodified aerobic composting composite membrane and the polydopamine modified membrane with different self-polymerization times under simulated composting conditions was tested using a homemade gas permeation device. First, the membrane was placed in the gas permeation device, and a wire mesh was placed on the low-pressure side of the membrane, and the gas permeator was sealed with bolts. Then, the valve of the gas cylinder was opened, and ammonia standard gas with a concentration of 500±10 ppm and 60°C water vapor were introduced at a rate of 0.4 L / min and 2.75 mL / min, respectively. The ammonia concentration of the outflowing gas was continuously measured at the outlet using a handheld pump suction detector. The ammonia gas retention rate was calculated as shown in formula (2).
[0084] (2)
[0085] Where: —Ammonia gas retention rate, %;
[0086] C 0 —Ammonia inlet concentration, ppm;
[0087] C 1 —Ammonia outlet concentration, ppm;
[0088] t —Test time, min.
[0089] Figure 6The figure shows the changes in ammonia outlet concentration and ammonia retention rate of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times in the ammonia barrier experiment. It can be seen that in the whole process, the ammonia outlet concentration of the polydopamine modified membrane is not higher than that of the unmodified aerobic composting composite membrane, indicating that the polydopamine modification can improve the ammonia retention effect of the membrane to a certain extent. This is because the large amount of hydroxyl and amino groups contained in the polydopamine in the modified membrane can hydrogen bond with ammonia, hindering the outward diffusion of ammonia, and the condensed water coverage area under the membrane increases after the modification, which increases the amount of ammonia dissolved in the water film, and reduces the open pores that allow ammonia to directly pass through the membrane (surface). In addition, the reduction in membrane porosity also has a positive effect on enhancing the barrier effect of ammonia.
[0090] Moreover, with the increase of polydopamine self-polymerization time, the ammonia interception effect of the membrane gradually increased. When the polydopamine self-polymerization time was 2 h and 4 h, the membrane had better ammonia barrier performance, and the ammonia interception rate could be maintained at 63.05%~64.46% and 65.46%~66.27%, respectively, which was 7.57% and 9.79% higher than that of the unmodified aerobic composting composite membrane.
[0091] (6) Determination of air permeability
[0092] Nitrogen and oxygen were used as test gases at room temperature, and the membrane was tested by a homemade gas permeation device. The membrane was placed in the gas permeation device, and a wire mesh was placed on the low-pressure side of the membrane, and then the gas permeator was sealed with bolts. The valve of the gas cylinder was opened, and the gas flow rate was adjusted so that the pressure difference on both sides of the inner membrane of the gas permeator was constant at 500 Pa. An air bag was used to connect the exhaust pipe at the outlet to collect the gas, and the collection time was 10 min. The nitrogen and oxygen gas permeation rates are shown in formula (3):
[0093] (3)
[0094] Where: GTR —Nitrogen and oxygen gas permeability, L / (m 2 ·s);
[0095] V —Gas permeation volume, L;
[0096] t —Test time, min;
[0097] A —Effective test area, cm 2 .
[0098] Figure 7The figure shows the changes in nitrogen and oxygen permeability of the unmodified aerobic composting composite membrane and the modified aerobic composting composite membrane at different self-polymerization times. It can be seen that the nitrogen and oxygen permeability of the modified aerobic composting composite membrane only decreases slightly compared with the unmodified aerobic composting composite membrane. Therefore, harmless gases such as nitrogen and oxygen can be quickly discharged from the modified membrane, and the membrane still has high air permeability.
[0099] In summary, the modified aerobic composting composite membrane provided by the present invention can simultaneously improve the moisture permeability and nitrogen retention and ammonia barrier efficiency of the membrane. Stable polydopamine is formed on the inner surface of the aerobic composting composite membrane using dopamine self-polymerization technology. The moisture permeability of the modified membrane under the optimal preparation parameters can be increased by 10.27% compared with the unmodified aerobic composting composite membrane, and the ammonia retention rate is increased by 7.57%. At the same time, it has higher air permeability, and can also maintain the excellent waterproof, splash-proof, tensile and heat-insulating properties of the original membrane.
[0100] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A modified aerobic composting composite membrane, characterized in that: It consists of a modified polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence; The modified polyester fiber layer includes a first polyester fiber layer and polydopamine wrapped around each fiber on the surface of the first polyester fiber layer; During the preparation of the polydopamine, the self-polymerization time of the dopamine hydrochloride solution on the surface of the first polyester fiber layer is 1 to 4 hours; The porosity of the modified aerobic composting composite membrane is 57-63%.
2. The modified aerobic composting composite membrane according to claim 1, characterized in that: The thickness of the first polyester fiber layer is 0.38-0.45 mm; the thickness of the polytetrafluoroethylene layer is 4-30 μm; and the thickness of the second polyester fiber layer is 0.38-0.45 mm.
3. The method for preparing the modified aerobic composting composite film according to claim 1 or 2, characterized in that: The following steps are involved: pre-treating the aerobic composting base film to obtain a pre-treated base film; The aerobic composting base film comprises a first polyester fiber layer, a polytetrafluoroethylene layer and a second polyester fiber layer stacked in sequence; The pretreated base film is placed in a dopamine hydrochloride solution so that the first polyester fiber layer of the pretreated base film contacts the dopamine hydrochloride solution and the second polyester fiber layer contacts the air, and then the polydopamine surface is self-polymerized to obtain the modified aerobic composting composite film.
4. The preparation method according to claim 3, characterized in that: The dopamine hydrochloride solution is obtained by mixing a Tris-HCl buffer solution and dopamine hydrochloride.
5. The preparation method according to claim 4, characterized in that: The concentration of the Tris-HCl buffer solution is 50-100 mmol / L; the pH value of the Tris-HCl buffer solution is 8.2-8.8; The concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 0.1-2 g / L.
6. The preparation method according to claim 3, characterized in that: The time for the self-polymerization of the polydopamine surface is 1 to 4 hours.
7. The preparation method according to claim 3 or 6, characterized in that: The polydopamine surface self-polymerization is carried out under stirring conditions, and the stirring is magnetic stirring; the rotation speed of the magnetic stirring is 200-500 r / min.
8. The preparation method according to claim 3, characterized in that: After the polydopamine surface is self-polymerized, the method further includes washing the composite membrane on which the polydopamine is polymerized with water and then drying it.
9. The preparation method according to claim 8, characterized in that: The drying temperature is 60-80° C., and the drying time is 8-24 h.
10. The method for using the modified aerobic composting composite membrane according to claim 1, characterized in that: When the modified aerobic composting composite membrane is used, the modified polyester fiber layer is used as the innermost layer.
Citation Information
Patent Citations
Polydopamine modified nanofiber coating-based nanofiltration membrane and preparation method thereof
CN111644078A
Polytetrafluoroethylene composite film for compost fermentation and processing technology thereof
CN117067737A